Developmental differences in motivation for participating in competitive swimming - Brodkin, P.; Weiss, M. R. (Journal of Sport & Exercise Psychology, 1990)
Motivations for participating in competitive swimming were evaluated for a wide range of age-groups. Factors and the ranking of responses by age-groups are listed.